2020
DOI: 10.1186/s12974-020-01820-6
|View full text |Cite
|
Sign up to set email alerts
|

The relationships between neuroinflammation, beta-amyloid and tau deposition in Alzheimer’s disease: a longitudinal PET study

Abstract: Background: The aim of this longitudinal study was to assess with positron emission tomography (PET) the relationship between levels of inflammation and the loads of aggregated β-amyloid and tau at baseline and again after 2 years in prodromal Alzheimer's disease. Methods: Forty-three subjects with mild cognitive impairment (MCI) had serial 11 C-PK11195 PET over 2 years to measure inflammation changes, and 11 C-PiB PET to determine β-amyloid fibril load; 22 also had serial 18 F-Flortaucipir PET to determine ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
104
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(122 citation statements)
references
References 38 publications
6
104
0
Order By: Relevance
“…Using transgenic PS1-APP mice, an established model of AD, Hickman et al demonstrated that the continuous production of proinflammatory cytokines reduces the expression of the phagocytosis receptors expressed in microglia and alters their functions ( 109 ). The sustained activation of microglia cells has been shown to exacerbate both amyloid and tau pathology and may serve as a link in the pathogenesis of AD ( 110 , 111 ). Indeed, the prolonged activation results in an impaired clearance of Aβ and increased accumulation in the CNS ( 112 ).…”
Section: Neuroinflammation: At the Center Of The Infectious Hypothesimentioning
confidence: 99%
“…Using transgenic PS1-APP mice, an established model of AD, Hickman et al demonstrated that the continuous production of proinflammatory cytokines reduces the expression of the phagocytosis receptors expressed in microglia and alters their functions ( 109 ). The sustained activation of microglia cells has been shown to exacerbate both amyloid and tau pathology and may serve as a link in the pathogenesis of AD ( 110 , 111 ). Indeed, the prolonged activation results in an impaired clearance of Aβ and increased accumulation in the CNS ( 112 ).…”
Section: Neuroinflammation: At the Center Of The Infectious Hypothesimentioning
confidence: 99%
“…It has been reported that APBA2 is involved in the MAPK signaling pathway and it alters cell viability, migration, and invasion [52]. However, the relationship between amyloid activity and neuroin ammation has been reported [54]; the role of in ammation in auditory hearing loss relief should be explored in further studies.…”
Section: Discussionmentioning
confidence: 96%
“…R -[ 11 C]PK11195, combined with tracers for Aβ and tau protein, revealed a biphasic neuroinflammation pattern in AD patients: initially, the R -[ 11 C]PK11195 signal was high in subjects bearing low Aβ levels and mild cognitive impairment (MCI) but, eventually, R -[ 11 C]PK11195 levels decreased as Aβ loads rose to pathological levels. At this later phase, the tau protein levels increased, and prompted the second wave of microglial activation, reaching the pathological phenotype of concomitant high levels of Aβ and tau protein and cognitive deterioration [ 193 ]. Similarly, the signal of the second-generation TSPO tracer [ 11 C]PBR28 was elevated in more than 50 MCI patients, potentially indicating a protective microglial activation at early AD [ 194 ].…”
Section: Imaging Redox Biomarkers Of Neuroinflammation In the Clinicmentioning
confidence: 99%